Numerical investigation on the seismic behaviour of GFRP-reinforced concrete rectangular columns. (1st July 2022) - Selmy, Yasser M.; El-Salakawy, Ehab F.
Highlights: Numerical analysis of the seismic response of GFRP-RC rectangular columns was conducted. All specimens reached the minimum 2.5% drift ratio specified by the Canadian standards. The effect of high axial load levels on reducing the drift capacity of GFRP-RC columns is more significant when low concrete strength is used. Stirrup spacing limit of sixteen times the diameter of the smallest longitudinal bar, provided by the Canadian standards, is very conservative. Increasing the column aspect ratio marginally affected the seismic behaviour of the modelled GFRP-RC columns. Abstract: Numerical analysis was performed using a nonlinear finite element software to investigate the seismic performance of glass fibre-reinforced polymer (GFRP)-reinforced concrete (RC) rectangular columns. Cyclic behaviour of reinforcement and concrete properties, based on fracture energy and bond–slip relationships between concrete and GFRP reinforcement, have been incorporated in the constructed finite element models (FEMs). Previous results obtained from testing seven full-scale GFRP-RC rectangular columns were used for the validation of the FEMs. The validated FEMs were used to conduct a parametric study on a wide range of key parameters affecting the behaviour of GFRP-RC columns under seismic loading, including concrete strength, axial load level, size and spacing of transverse reinforcement, and shear span-to-depth ratio. An improvement in the capacity of GFRP-RC columns was observed by increasing the concrete strength and decreasing spacing of transverse reinforcement. However, the lateral load capacity was reduced with increasing axial load level, which ultimately resulted in a premature failure of the GFRP-RC columns. The mode of failure and deformation characteristics changed significantly due to reduction in span-to-depth ratio.